2012
DOI: 10.3892/ol.2012.792
|View full text |Cite
|
Sign up to set email alerts
|

Specific organ metastases and survival in small cell lung cancer

Abstract: Abstract. The aim of our retrospective study was to evaluate the clinicopathological features associated with distant metastasis from small cell lung cancer (SCLC). We reviewed patients diagnosed with SCLC metastasis at the time of presentation between 1999 and 2010. Among the consecutive 251 SCLC patients diagnosed, 152 (60.6%) patients had distant metastasis, of which 20.3, 18.3, 15.5, 10.0 and 6.0% of patients had liver, bone, brain, lung and adrenal gland metastasis, respectively. In a multivariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 18 publications
15
102
2
1
Order By: Relevance
“…In non-SCLC (NSCLC) as well as in SCLC, bone metastases indicated poor survival in population-based cohort studies [3,8]. In SCLC, patients with bone metastases also experienced poor survival in a study by Nakazawa et al [9] and in a population-based cohort study, which is consistent with our results. In our study, bone metastases were found in 26.2% of all patients with SCLC and 34.3% of the patients with SCLC-ED.…”
Section: Discussionsupporting
confidence: 82%
“…In non-SCLC (NSCLC) as well as in SCLC, bone metastases indicated poor survival in population-based cohort studies [3,8]. In SCLC, patients with bone metastases also experienced poor survival in a study by Nakazawa et al [9] and in a population-based cohort study, which is consistent with our results. In our study, bone metastases were found in 26.2% of all patients with SCLC and 34.3% of the patients with SCLC-ED.…”
Section: Discussionsupporting
confidence: 82%
“…Postmortem analysis in both groups revealed that tumors had grown within the thoracic cavity or in the parathoracic region ( Figure 4, A and B). Some mice exhibited spontaneous metastases to the liver ( Figure 4A), which was not observed in the subcutaneous model; the liver is the most common site of distant metastases in SCLC patients (25). Monitoring tumor growth over time by bioluminescence imaging, we found that in this context, the CD47-blocking antibody also produced a significant inhibition of tumor growth ( Figure 4, C and D).…”
Section: Cd47-blocking Antibodies Induce Phagocytosis Of Sclc Cells Bmentioning
confidence: 72%
“…Lung cancer metastasis to vascular-and lymphatic-associated organs is frequent and the most common metastatic sites are the lung, bone and brain (4)(5)(6). Lymph node involvement is primarily regional in cancers of the internal organs, including lung cancer (4,7).…”
Section: Discussionmentioning
confidence: 99%